Improving Children’s Short Story Writing Skills Through the BUHAR (Diary) Programme in Grade V Elementary School - Idammatussilmi, Idammatussilmi; Wahyuningsih, Effi; Ifadah, Luluk (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2025)
Short story is one of the literary works that is poorly understood by students. This is due to the lack of ability of students in expressing ideas and composing sentences into a paragraph. The purpose of this study was to determine the improvement of children's short story writing skills through the BUHAR programme. This research is action research that applies the Kemis Taggart model which consists of planning, action, observation and reflection. The research data included quantitative data obtained through questionnaires and written tests whose results were analysed through SPSS. While qualitative data obtained through observation, interviews (teachers, students, guardians), journals analysed by data reduction, data presentation, and conclusion drawing. The results showed that the application of the BUHAR programme helped improve children's short story writing skills. This was achieved through several indicators that appeared in each cycle. These indicators include improvements in several ways: (1) the average score on each component of writing children's short stories, namely 45 in the initial test to 60.4 (post-test 1), and 78.3 (post-test 2); (2) the assessment category from ("sufficient") to ("good"); (3) the increase in learning outcomes from 0.28 (cycle 1) and 0.61 (cycle 2); (4) the number of existing students (100%) experienced an increase in the skill of writing children's short stories; (5) Increased motivation of students as seen from their participation and positive response during the BUHAR programme.